The Influence of the Use of Fluid and Thermodynamics KIT on Conceptual Shifts in Dynamic Fluid Material - Dewi Astuti Saromeng; Asri Arbie; Abdul Haris Odja (Jurnal Pijar MIPA, 2026)
Physics learning often causes students to experience misconceptions, especially in fluid dynamics material. This study aims to analyze the effect of the use of the Fluid and Thermodynamics KIT on the shift in students' conceptions. This study used a quantitative approach with a one–group pretest–posttest design involving three experimental classes (replications 1 and 2) and a total of 90 students. The instrument used was a three-tier test to identify conception categories. Data analysis techniques were carried out using descriptive statistical analysis in the form of a percentage of conception shifts classified into positive shifts (↑), negative (↓), and no effect (ꓳ). The results showed that the Fluid and Thermodynamics KIT was characterised by positive conception shifts across all classes. The highest percentage of positive shifts was in the experimental class (73%), followed by replication 2 (56.33%) and replication 1 (53%). The negative shifts were 30%, 25.67%, and 15.67%, respectively, while the no-effect category was 17%, 21.33%, and 28%, respectively, in the experimental class, replication 1, and replication 2. These findings indicate that the Fluid and Thermodynamics KIT is effective in facilitating conceptual reconstruction and improving students' understanding of fluid dynamics.